Postgraduate Research on International Tertiary Students: The Case of Malaysia - Mustapha, Sit Maziha; Syed Ahmad, Shariffah Bahyah; Siow, Heng Loke (2023)
This paper sought to enumerate theses produced by postgraduate researchers of Malaysian universities that focus on international students enrolled in Malaysian tertiary institutions. Using the Malaysian Theses Online (MyTO) and the university libraries’ Online Public Access Catalogue (OPAC) databases to gather the initial data, this paper went on to present metadata about the researchers as well as the participants of these postgraduate studies. It concluded that though there has been quantitative progress since the first thesis on international students was produced in 1999, there is a need to address the unevenness of focus that was leaning more towards the experiences of postgraduate students in public institutions of higher learning and less on those enrolled in undergraduate programs, especially at private institutions of higher learning in Malaysia.